(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The study included the effect of chitosan and nystatin on animals treated with C. krusei on blood parameters, electrolytes and intestinal tissue. Domestic male rabbits were used in this study, which indicated a noticeable rise in the concentration of Hb and PCV in the blood of the Chitosan group compare to the control group and a significant decrease in the C. krusei and C group, While the results revealed a noticeable rise in W.B.C in the blood of the treated group Chitosan, C. krusei, C. krusei + Chitosan, and C. krusei + Nystatin compared to the control group. It was found from the results in a table (2) that there was a considerable decrease (P<0.05) in the level of K+ concentration in the blood serum in C. krusei group, C. krusei + Chitosan group, and C. krusei + Nystatin group compared to a control group. While the findings indicated that there was a significant increase in the concentration of Na+ in the blood serum in the treated group C. krusei and group C. krusei + Chitosan and C. krusei + Nystatin group compared with the control group and a significant decrease in the Chitosan group compared to the control group, while it showed a significant decrease in Ca + concentration in group C. krusei+Nystatin compare to the control group. Through the results, it was discovered that there were no significant differences in the concentration of Mg + in all groups in the blood serum compared to the control group. The results of the microscopic examination in the four groups of intestinal tissue showed the appearance of necrosis and lysis in the cells lining the villi, fluttering and blood congestion with the proliferation of inflammatory cells in abundance in addition to the occurrence of hyperplasia in the mucous layer of the intestine.